Drive Rigidity Characteristic Analysis of Telescopic Electric Cylinder used in Neutron Spectrometer - Peng Fuxia; Wu Yunxin; Gong Hai; Li Yang; Zhang Yu (Jixie chuandong)
The design of neutron spectrometer sample,which is developed by our country is briefly introduced. Based on Hertz contact theory and the structural features of telescopic electric cylinder used in the neutron spectrometer,the theoretical model of telescopic electric cylinder drive rigidity is established and the numerical calculation is carried out. The load- drive rigidity curve is obtained by calculating rigidity under different axial loads. The impact factor is defined to analyze the degree of the weight of each deformation of transmission stiffness,and the impact factor of deformation of different parts are calculated and analyzed to find the weak links of the rigidity. Some measures are taken to improve the rigidity,the basis for accuracy of telescopic electric cylinders is provided. Finally,the finite element model is analyzed by using ANSYS Workbench,the analysis results with the theoretical value is an error of 8. 1%,the correctness of theoretical analysis is verified.